Agraryzm i jego wyraz w myśli społeczno-ekonomicznej F. Bujaka, W. Stysia i W. Grabskiego - Kowalczyk, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Scientific interests of F. Bujak, W. Stys and W. Grabski focused on agriculture and agricultural policy. During the inter-war period, they represented the so-called professorial trend in the development of the agrarian thought. They pointed out the need to improve the situation of the peasants and introduce an agricultural reform. While supporting the dissemination of property, they advocated for increasing the amount of land owed by peasants. Additionally, they suggested buying land by the state, and opposed to the parceling land without compensation. They also advocated for building a fair socio-economic political system, and liquidation of exploitation. Finally, they underlined the importance of cooperatives in the process of spreading economic and civilization progress in rural areas.
Keywords: Grabski, Władysław (1874-1938); Bujak, Franciszek (1875-1953); Styś, Wincenty (1903-1960); myśl społeczno-ekonomiczna; agraryzm; II Rzeczpospolita 1918-1939